Interannual evaluation of the regenerative strategies of the exotic invasive species Gleditsia triacanthos compared with the native Acacia aroma in the Chaco Serrano Woodland of Cordoba (Argentina) - Ferreras, Ana Elisa; Funes, Guillermo; Galetto, Leonardo (Bosque (Valdivia), 2017)
It has been proposed that exotic species, compared with native ones, differed in certain characteristics that may favor their expansion. The regenerative characteristics of exotic species may vary among reproductive seasons, modifying the patterns observed contrasted with native species and hence influencing their expansion velocity. In this work, fruit production, seed density in the soil and seedlings density around the con-specifics and in the study sites were compared between the exotic invasive Gleditsia triacanthos and the native Acacia aroma. The study was developed in at least two reproductive seasons, in areas of the Chaco Serrano Woodland of Córdoba (Argentina). In each season, the number of fruits was counted. Around the con-specifics of each species it was obtained: a) the density of seeds in the soil (in two different moments per year) and b) the density of seedlings. In addition, the density of seedlings distributed in the study sites was registered. In two of the three reproductive seasons analyzed, fruit production was higher in the exotic invasive species. In both seasons the density of seeds in the seed bank and of seedlings around the focal individuals was higher in the exotic species. The density of seedlings in the study sites did not vary between species in any of the seasons. The regenerative characteristics observed in G. triacanthos and the consistency in their response in different reproductive seasons suggest a rapid expansion of the species in the region.